Innovation Research Based on Global Entrepreneurship Monitor (GEM) Project: Review of the Last Decade (2017)
ABSTRATC: Research on innovation and entrepreneurship has increased in recent years. This article explores the structure of innovation research based on Global Entrepreneurship Monitor (GEM) project. A search of articles containing innovation and GEM related words was conducted, including only those published in journals within the Thomson Reuters' Social Sciences Citation Index®. The main findings of this study show that is feasible use GEM's data set to do research on innovation. Models that treat new firm creation and innovation as separate aspects of entrepreneurship, as well as, determinants of economic growth could be conceptualize and test with data provide by GEM project. Also, the number of innovations articles using GEM' database has increased in recent years, suggesting opportunities and challenges for future research